The Neural Cell Adhesion Molecule Promotes FGFR-Dependent Phosphorylation and Membrane Targeting of the Exocyst Complex to Induce Exocytosis in Growth Cones - Chernyshova, Yana (J Neurosci, 2011)
The exocyst complex is an essential regulator of polarized exocytosis involved in morphogenesis of neurons. We show that this complex binds to the intracellular domain of the neural cell adhesion molecule (NCAM). NCAM promotes FGF receptor-mediated phosphorylation of two tyrosine residues in the sec8 subunit of the exocyst complex and is required for efficient recruitment of the exocyst complex to growth cones. NCAM at the surface of growth cones induces Ca(2+)-dependent vesicle exocytosis, which is blocked by an inhibitor of L-type voltage-dependent Ca(2+) channels and tetanus toxin. Preferential exocytosis in growth cones underlying neurite outgrowth is inhibited in NCAM-deficient neurons as well as in neurons transfected with phosphorylation-deficient sec8 and dominant-negative peptides derived from the intracellular domain of NCAM. Thus, we reveal a novel role for a cell adhesion molecule in that it regulates addition of the new membrane to the cell surface of growth cones in developing neurons.